Translation of personal official documents: Examining Australian norms and practice - Taibi, Mustapha; Ozolins, Uldis (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2023)
Despite their potential real-life impact, translations of personal official documents have been largely unexplored in translation scholarship. Little research has been undertaken into professional practice within this translation domain and, correspondingly, little is known about how different stakeholders approach the necessary quality assurance. In this paper we examine the professional context of the translation of personal official documents in Australia by considering the perspectives of NAATI-certified translators, translation agencies and receiving institutions. We report the findings of three surveys on quality, integrity and authenticity in official personal document translation, comparing the views of these three key stakeholders. There is general agreement that ensuring quality and integrity in this area requires that accuracy be accorded close attention and the official features of original documents be documented. Yet, these guidelines are simpler in theory than in practice with its various issues and uncertainties, including occasional translation errors, the risks of extract translations, varying levels of quality assurance and lack of clear and consistent guidelines from language service providers and government organisations.